AMICO galaxy clusters in KiDS-DR3: constraints on ΛCDM from extreme value statistics - Busillo, Valerio; Covone, G; Sereno, M; Ingoglia, L; Radovich, M; Bardelli, S; Castignani, G; Giocoli, C; Lesci, G F; Marulli, F; Maturi, Matteo; Moscardini, L; et al. (Monthly notices of the Royal Astronomical Society, 2023)
We constrain the ΛCDM cosmological parameter σ8 by applying the extreme value statistics for galaxy cluster mass on the AMICO KiDS-DR3 catalogue. We sample the posterior distribution of the parameters by considering the likelihood of observing the largest cluster mass value in a sample of Nobs = 3644 clusters with intrinsic richness λ* > 20 in the redshift range z ∈ [0.10, 0.60]. We obtain $σ _{8}=0.90_{-0.18}^{+0.20}$, consistent within 1σ with the measurements obtained by the Planck collaboration and with previous results from cluster cosmology exploiting AMICO KiDS-DR3. The constraints could improve by applying this method to forthcoming missions, such as Euclid and LSST, which are expected to deliver thousands of distant and massive clusters.
Veröffentlicht: 21. Juli 2023
Gesehen am 06.10.2023